Engenharia de reservatórios com temperaturas efetivas arbitrárias e máquinas térmicas quânticas para sistemas de spins nucleares - Mendonça, Taysa Mendes de (2021)
In this work we show how to engineer reservoirs with different effective temperatures for a single qubit (quantum bit) system. To that end, we built an appropriate interaction between a qubit, that is, a 13C nuclear spin, and a reservoir, in our case, a large number of nuclear hydrogen spins that act as a spin bath. For this study, we used the carbon-hydrogen structure present in the polycrystalline sample of adamantane. The interaction we seek is built by applying a sequence of specific radiofrequency pulses using the technique of nuclear magnetic resonance (NMR). The temperature of the entire system can be controlled by preparing the initial state of the nuclear hydrogen spins and, thus, we show how to build reservoirs with arbitrary temperatures, including negative effective ones. As an application of these artificial reservoirs, we investigated the implementation of quantum thermal machines. First, we performed an experiment in which a quantum thermal machine works under two reservoirs, one at a positive and the other at an effective negative spin temperature. We use the liquid chloroform molecule to simulate the qubit system. We show that the efficiency of this thermal machine can be greater than the case when the two reservoirs are at positive temperatures. We also demonstrate a counterintuitive result, in which the efficiency of the Otto cycle can be surpassed and when the quantum thermal machine operates in a finite time, that is, in a non-adiabatic manner. Finally, we implemented a quantum thermal machine that operates in a single reservoir at an effective negative temperature whose efficiency is always 100%, regardless of the unitary transformation carried out on the qubit, as long as its final state is different from its initial one. In this experiment we again use the carbon-hydrogen structure present in the polycrystalline sample of adamantane. As far as we know, this is the simplest and most efficient quantum thermal machine ever built. For all steps, we show that the theoretically predicted results are in very good agreement with the experimental data.